The Effect Of Content Creators And Customer Reviews On Consumer Purchase Interest In Tiktok Social Media - Susanti Ningsih; Koerniawan Hidajat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The currently growing TikTok social media presents an opportunity for entrepreneurs to promote products and services to consumers through digital marketing. The thing that sellers do to increase sales is to consistently create interesting and viral content. Creativity in content creation is needed whose impact will be very influential in attracting buyer interest and changing consumer perceptions. This study aims to determine and explain the effect of content creators and customer reviews on consumer buying interest in TikTok social media. Quantitative research method. Questionnaire data collection with a Likert scale. Data analysis with SmartPLS. The results show that content creators have an effect on buying interest and customer reviews have no effect on buying interest.